Pengaruh Lama Penyimpanan Pengencer Tris Kuning Telur Terhadap Motilitas Spermatozoa Sapi Simental di BIB Banyumulek Provinsi Nusa Tenggara Barat - Janah, Maratun; Arifpansyah, Akbar; Atma, Candra Dwi; Dharmawibawa, Iwan Doddy (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Tris yolk is a diluent that can be used to maintain and protect spermatozoa during storage so that they can be used in the process of artificial insemination. The length of storage greatly affects the motility and viability of spermatozoa in semen. The purpose of this study was to determine the effect of long storage of egg yolk tris diluent on the motility and viability of simental bovine spermatozoa. This research was carried out at the Banyumulek Artificial Insemination Center Laboratory, West Nusa Tenggara Province, from July to Desember 2024. The study of the effect of long storage of egg yolk tris diluent on the motility and viability of simental bovine spermatozoa used a randomized experimental method complete with four treatments and six repeats. Each treatment, namely P1, P2, P3, and P4, was carried out by mixing 0.075 ml of semen and 0.3 ml of egg yolk tris diluent stored for 24, 48, 72, and 96 hours. The data obtained were processed by variety analysis method (ANOVA) and Duncan's further test. The results showed that P1 treatment with a storage period of 24 hours resulted in the highest average motility and viability values of 63.33 ± 6.055 % for motility and 63.50 ± 6.892 % for spermatozoa viability. P4 treatment with a storage period of 96 hours still showed a good mean value with motility values of 40.83 ± 7.360 % and spermatozoa viability of 53.50 ± 12.112 %. Thus, egg yolk tris is suitable for use as a semen thinner for artificial insemination because it is able to maintain the motility and viability of spermatozoa even for a long time of 96 hours.